INTEGRATING TWO THEORIES TO ANALYZE FRUIT PURCHASING INTENTIONS: A CONCEPTUAL STUDY - Fasyni, Awisal; Muthusamy, Geetha; Wahid, Siti Daleela Mohd; Mohamad, Wan Normila (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Encouraging fruit purchases by consumers aims to tackle public health concerns while simultaneously enhancing the fruit industry in Indonesia. This research seeks to provide a framework based on a literature review to clarify the factors influencing customers' intention to purchase fruits. A thorough literature study on fruit purchase intention was performed to establish a conceptual framework grounded in the Theory of Planned Behavior and the Theory of Consumption Values. The conceptual model will aid practitioners in understanding the influence of consumer consumption values and attitudinal variables on improving purchase intention.